2005
DOI: 10.1093/gerona/60.12.1563
|View full text |Cite
|
Sign up to set email alerts
|

Are Preoperative Depressive Symptoms Associated With Postoperative Delirium in Geriatric Surgical Patients?

Abstract: Preoperative screening for the presence of depressive symptoms can be performed easily in elderly patients, and yields useful prognostic information relating to postoperative delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 36 publications
6
82
1
5
Order By: Relevance
“…Ameliyat öncesi dönemde özellikle depresyon başta olmak üzere diğer psikiyatrik semptomların varlığı-nın postoperatif deliryum için yatkınlık oluşturduğu bildirilmiştir (10,14,15) . Tüm yatan hastalar deliryum için risk altında olmasına rağmen, özellikle kardiyak cerrahi uygulanan hastalar deliryuma daha yatkındırlar.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ameliyat öncesi dönemde özellikle depresyon başta olmak üzere diğer psikiyatrik semptomların varlığı-nın postoperatif deliryum için yatkınlık oluşturduğu bildirilmiştir (10,14,15) . Tüm yatan hastalar deliryum için risk altında olmasına rağmen, özellikle kardiyak cerrahi uygulanan hastalar deliryuma daha yatkındırlar.…”
Section: Discussionunclassified
“…Deliryum tablosu için tanımlanan çok sayıdaki risk faktörlerinin ise; ileri yaş, serebral iskemi, atriyal fibrilasyon, anemi, uzamış entübasyona bağlı uzun süreli benzodiyazepinler ve opiodler ile sedasyon, ameliyat süresi ve demans olduğu belirtilmektedir (1,2) . Ailede psikiyatrik hastalık öyküsünün bulunması ve ameliyat öncesi dönemde özellikle depresyon başta olmak üzere diğer psikiyatrik semptomların varlığının postoperatif deliryum için yatkınlık oluşturduğu bildirilmiştir (10,14,15) . Tüm yatan hastalar deliryum için risk altında olması-na rağmen, özellikle kardiyak cerrahi uygulanan hastalar deliryuma daha yatkındırlar.…”
Section: Introductionunclassified
“…Twenty two of these studies reported alcohol use/misuse prevalence ( Table 1) and 19 evaluated alcohol-related post-operative complications ( Table 2). Seven of the 27 studies described alcohol use or misuse in mixed samples of patients undergoing different types of non-cardiac surgeries [22][23][24][25][26][27][28], and three of those seven used data from the Veterans Affairs (VA) National Surgical Quality Improvement Program (NSQIP) [22][23][24]. One other study described and compared the prevalence of alcohol misuse across different surgical subspecialties [29], and one study was limited to vascular or thoracic patients admitted to ICU post-operatively [30].…”
Section: Studies Meeting Inclusion Criteria For Reviewmentioning
confidence: 99%
“…In 3 studies of patients undergoing major non-cardiac surgery, the prevalence of medical record documentation of drinking more than 2 drinks per day in the 2 weeks prior to patient surgery were 9.6% in patients > 65 years old at one site [25] and 15.2% and 11.2% in 2 large multisite studies [22,23]. Another study of major non-cardiac surgery patients found that 7.7% reported "…a current problem drinking too much alcohol" [27].…”
Section: Prevalence Of Alcohol Use and Misuse In Us Surgical Patientsmentioning
confidence: 99%
“…Depression was shown to be an independent predictor of postoperative delirium (Leung et al, 2005;Smith et al, 2009), infectious complications (Doering et al, 2008), and overall increased morbidity and mortality at postoperative period (Goyal et al, 2005;Connerney et al, 2010). Increased anxiety in the early postoperative period was demonstrated to be a predictor of postoperative atrial fibrillation (Tully et al, 2011a), whereas baseline anxiety disorder was shown to be significantly associated with increased cardiac morbidity and mortality after coronary artery and valve surgery (Szekely et al, 2007;Tully et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%